2017
DOI: 10.3389/fpls.2017.01634
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping by Whole Genome Re-sequencing and Analysis of Candidate Genes for Nitrogen Use Efficiency in Rice

Abstract: Nitrogen is a major nutritional element in rice production. However, excessive application of nitrogen fertilizer has caused severe environmental pollution. Therefore, development of rice varieties with improved nitrogen use efficiency (NUE) is urgent for sustainable agriculture. In this study, bulked segregant analysis (BSA) combined with whole genome re-sequencing (WGS) technology was applied to finely map quantitative trait loci (QTL) for NUE. A key QTL, designated as qNUE6 was identified on chromosome 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…Previous studies have shown that the differences between NIL15 and NIL19 are on chromosomes 6, 8, 9, and 10 [5] . These regions contain 6 PTR genes, which were LOC_Os06g13200, LOC_Os06g13210, LOC_Os06g15370, LOC_Os06g21900, LOC_Os06g38294, and LOC_Os10g22560.…”
Section: The Expression Profiles Of Ptr Genes In Near Isogenic Linesmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that the differences between NIL15 and NIL19 are on chromosomes 6, 8, 9, and 10 [5] . These regions contain 6 PTR genes, which were LOC_Os06g13200, LOC_Os06g13210, LOC_Os06g15370, LOC_Os06g21900, LOC_Os06g38294, and LOC_Os10g22560.…”
Section: The Expression Profiles Of Ptr Genes In Near Isogenic Linesmentioning
confidence: 93%
“…The information about the two lines can be found in previous studies [5] . The evenly germinated seeds were selected and cultured in 96-well cultivation instrument with 1.4 mM NH 4 NO 3 (high nitrogen, HN) nutrient solution.…”
Section: Plant Materials and Hydroponicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, QTL-Seq approach was applied to fine-map bacterial wilt resistance genes and develop diagnostic markers for use in breeding in the case of groundnut (Luo et al 2019a). Adoption of QTL-Seq is increasingly reported for delineating candidate QTLs for both qualitative and quantitative traits (Yang et al 2017;Li et al 2018;Zhang et al 2018;Clevenger et al 2018;Zhang et al 2019;Luo et al 2019b).…”
Section: Role Of Ngs In Accelerating High-resolution Mapping and Genementioning
confidence: 99%
“…Recently, researchers have identified several loci that are associated with NUE in rice [3,4] . In the previous study, we identified a major QTL qNUE6 for rice NUE on chromosome 6 in rice, and LOC_Os06g15370 may be the ideal candidate gene [5] . The annotation for…”
Section: Introductionmentioning
confidence: 99%